2016
DOI: 10.7860/jcdr/2016/14591.7088
|View full text |Cite
|
Sign up to set email alerts
|

Oral Radiology Safety Standards Adopted by the General Dentists Practicing in National Capital Region (NCR)

Abstract: Introduction: With advancement in diagnostic techniques, the utilization of radiologic examination has risen to many folds in the last two decades. Ionizing radiations from the radiographic examination carry the potential for harm by inducing carcinogenesis in addition to the diagnostic information extracted. Radiation doses utilized in the course of dental treatment might be low for individual examinations but patients are exposed to repeated examinations very often and many people are exposed during the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
18
6
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 15 publications
8
18
6
4
Order By: Relevance
“…3,4 Majority of the present study subjects (94.3%) were of the opinion that routine radiographs should not be taken for all the patients, and most of them did not take routine full mouth (98.8%) and panoramic radiographs (95.4%) for their patients. These reports confirm the findings of Shahab et al 12 and Chaudhry et al 13 Lee and Ludlow, 14 however, reported that 34.1% of their study subjects preferred prescription of routine radiographs for their patients. Majority of the present study subjects thought that during pregnancy, only in case of emergencies, radiograph can be taken with appropriate radiation protection measures.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…3,4 Majority of the present study subjects (94.3%) were of the opinion that routine radiographs should not be taken for all the patients, and most of them did not take routine full mouth (98.8%) and panoramic radiographs (95.4%) for their patients. These reports confirm the findings of Shahab et al 12 and Chaudhry et al 13 Lee and Ludlow, 14 however, reported that 34.1% of their study subjects preferred prescription of routine radiographs for their patients. Majority of the present study subjects thought that during pregnancy, only in case of emergencies, radiograph can be taken with appropriate radiation protection measures.…”
Section: Discussionsupporting
confidence: 82%
“…[8][9][10][11][12][13] Although fewer studies are conducted in India pertaining to radiation protection, in-depth exploratory studies are sparse. There is need to identify the lacunae in radiation protection practices, so that the newer policies can be bought in or the existing ones could be reinforced according to the changes required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em contrapartida, alguns dentistas e/ou membros da equipe posicionam pessoalmente o filme radiográfico na cavidade oral do paciente, o que contradiz as normas de radioproteção 4 . Um estudo realizado na Índia observou que apenas 28,8% dos cirurgiões-dentistas obedeciam a distância preconizada entre operador e equipamento 19 . Outro método de radioproteção para operador é a blindagem, a qual consiste em barreiras constituídas de chumbo que atenuam os feixes de raios X. Ainda assim, há relatos de que uma pequena parcela dos dentistas se importa com a correta proteção nos consultórios odontológicos, enquanto outros se protegem de forma inadequada, com paredes sem barita de chumbo ou por distanciamento ineficaz, o que contradiz as medidas regulamentadoras da Portaria 453/1998 4,17 .…”
Section: Resultsunclassified
“…Unfortunately, only 20.7% used lead aprons on a regular basis which was almost similar to that obtained from study in Korea with a percentage of 21.7%, [11] and also agrees with a related study carried out among the Belgian dentists manifesting that 88% of dentists did not use lead aprons regularly. [18] This might be due to a lack of strict regulations regarding safe practice [19] or unavailability of lead aprons. In general, the results reflected poor awareness toward x-ray exposure and precautions, similar results revealed from others, [1,3,10] but from the literature; one study concluded that radiation protection measures were more significant amongst clinical specialists.…”
Section: Discussionmentioning
confidence: 99%